Czy istnieje idealny typ "opozycyjności"? - Pomorska, Marzena (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
Political opposition is a fundamental category of contemporary political analysis. On the one hand, it may be disorganized and it may express social opposition. On the other hand, it may be organized in the form of a political party. It may be legal or it may stand outside the law. It may be motivated by noble ideals or lust for power. It does not matter. However, the most important thing is that some kind of opposition always exist in all political systems and in all countries. Opposition is a political phenomenon.